Hypothermia-triggered biventricular Takotsubo cardiomyopathy: the octopus that survived the polar vortex. Issue 7 (27th July 2019) - Ajam, Mustafa; Shokr, Mohamed; Ajam, Firas; Afonso, Luis
Abstract : Takotsubo cardiomyopathy (TTC) is most commonly characterised by transient apical ballooning in response to physical or emotional stress without significant coronary artery disease (CAD). Various physical and emotional factors can trigger TTC. We report a case of hypothermia-induced biventricular TTC in an 84-year-old man admitted with a core body temperature of 29.8°C, followed by quick recovery of systolic function and resolution of wall motion abnormality after discharge. TTC should be suspected in hypothermic patients presenting with evidence of new onset heart failure and be added to the expanding list of factors triggering TTC. Similar to TTC induced by various other factors, hypothermia-induced TTC also carries a favourable prognosis with relatively quick recovery of wall motion abnormalities.